Peningkatan Hasil Belajar IPA Melalui Model Pembelajaran Auditory Intellectually Repetition (AIR) Pada Siswa Kelas IX 1 - Resyani Resyani (Universitas Negeri Makassar, 2021)
This study aims to improve science learning outcomes in class IX.1 students of SMP Negeri 1 Mallusetasi through the Auditory Intellectually Repetition (AIR) learning model for class IX.1 students of SMP Negeri 1 Mallusetasi. This type of research is a classroom action research which includes four stages, namely: planning, implementing the action, observing and reflecting. The results showed that based on data on student learning outcomes, students who completed according to the KKM in science subjects at the school were 88.89% or as many as 24 students. Thus, it has fulfilled the classical success indicator, which is 75%.